Consolidation of the clinical and genetic definition of a SOX4-related neurodevelopmental syndrome. Issue 11 (1st March 2022) - Angelozzi, Marco; Karvande, Anirudha; Molin, Arnaud N; Ritter, Alyssa L; Leonard, Jacqueline M M; Savatt, Juliann M; Douglass, Kristen; Myers, Scott M; Grippa, Mina; Tolchin, Dara; Zackai, Elaine; Donoghue, Sarah; et al.
Abstract : Background: A neurodevelopmental syndrome was recently reported in four patients with SOX4 heterozygous missense variants in the high-mobility-group (HMG) DNA-binding domain. The present study aimed to consolidate clinical and genetic knowledge of this syndrome. Methods: We newly identified 17 patients with SOX4 variants, predicted variant pathogenicity using in silico tests and in vitro functional assays and analysed the patients' phenotypes. Results: All variants were novel, distinct and heterozygous. Seven HMG-domain missense and five stop-gain variants were classified as pathogenic or likely pathogenic variant (L/PV) as they precluded SOX4 transcriptional activity in vitro. Five HMG-domain and non-HMG-domain missense variants were classified as of uncertain significance (VUS) due to negative results from functional tests. When known, inheritance was de novo or from a mosaic unaffected or non-mosaic affected parent for patients with L/PV, and from a non-mosaic asymptomatic or affected parent for patients with VUS. All patients had neurodevelopmental, neurological and dysmorphic features, and at least one cardiovascular, ophthalmological, musculoskeletal or other somatic anomaly. Patients with L/PV were overall more affected than patients with VUS. They resembled patients with other neurodevelopmental diseases, including the SOX11- related and Coffin-Siris (CSS) syndromes, but lacked the most specific features of CSS. Conclusion: These findings consolidate evidence of a fairly non-specific neurodevelopmental syndrome due to SOX4 haploinsufficiency in neurogenesis and multiple other developmental processes.